(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article highlights the socio-psychological features of the emergence of conflicts among high school students and approaches to finding solutions to conflicts. Differences in the behavior of girls and boys in conflict situations stem from both psychological and social factors. It systematically covers the psychological reactions of girls in conflict situations and the reasons for this.